Synthesis of C4-Linked C0- and C2-Imidazole 2′-Deoxyribonucleoside Phosphoramidites and Imidazole Base-Pairing Effects on DNA - Harusawa, Shinya; Yoneyama, Hiroki; Usami, Yoshihide; Yamamoto, Daisuke; Zhao, Zheng-yun (Synthesis, 2014)
The synthesis of C4-linked imidazole C0- and C2-2′-deoxyribonucleoside phosphoramidites (dPAs), in which the final phosphitylations are greatly improved by 4,5-dicyanoimidazole-promoted conversion, is described. The respective dPAs are successfully incorporated into the sequence of a 15-nt DNA, and the abilities of one or two imidazoles to pair with different bases are investigated through thermal melting (Tm) experiments on the resulting DNA duplexes. Furthermore, computational models of the imidazole-modified DNAs are found to be in good agreement with the results of the thermal melting experiments.
Keywords: imidazole; phosphoramidite; C-deoxyribonucleoside; base pairing; DNA